2021
DOI: 10.1242/jcs.246090
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear upregulation of class I phosphoinositide 3-kinase p110β correlates with high 47S rRNA levels in cancer cells

Abstract: The class I phosphoinositide 3-kinase (PI3K) catalytic subunits p110α and p110β are ubiquitously expressed but differently targeted in tumours. In cancer, PIK3CB (encoding p110β) is seldom mutated compared to PIK3CA (encoding p110α) but can contribute to tumorigenesis in certain PTEN-deficient tumours. The underlying molecular mechanisms are however unclear. We have previously reported that p110β is highly expressed in endometrial cancer (EC) cell lines and at the mRNA levels in primary patient tumours. Here, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…To support these findings, a minor pool of PtdIns(4,5) P 2 has been previously reported in the nucleolus and could hence substantiate the nucleolar synthesis of PtdIns(3,4,5) P 3 ( 21 , 62 ). In addition, the PPIn kinase isoforms, PI4K IIα, PIP5K Iα, and PI3K p110β which synthesize PtdIns4 P , PtdIns(4,5) P 2 , and PtdIns(3,4,5) P 3 respectively, have all been shown to be present in the nucleolus ( 25 , 28 , 97 , 98 ). Similarly, some evidence point to the presence of the PtdIns(3,4,5) P 3 phosphatases, phosphatase and tensin homolog and Src homology 2 domain–containing inositol phosphatase (SHIP) in the nucleolus ( 99 , 100 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To support these findings, a minor pool of PtdIns(4,5) P 2 has been previously reported in the nucleolus and could hence substantiate the nucleolar synthesis of PtdIns(3,4,5) P 3 ( 21 , 62 ). In addition, the PPIn kinase isoforms, PI4K IIα, PIP5K Iα, and PI3K p110β which synthesize PtdIns4 P , PtdIns(4,5) P 2 , and PtdIns(3,4,5) P 3 respectively, have all been shown to be present in the nucleolus ( 25 , 28 , 97 , 98 ). Similarly, some evidence point to the presence of the PtdIns(3,4,5) P 3 phosphatases, phosphatase and tensin homolog and Src homology 2 domain–containing inositol phosphatase (SHIP) in the nucleolus ( 99 , 100 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of PPIn metabolism and signaling occurring in the nucleus independently of the cytoplasm was reported shortly after in several studies ( 10 , 11 , 12 ). Consequently, with the exception of phosphatidylinositol 3,5-bisphosphate, the remaining six PPIns have been detected and/or quantified in the nucleus ( 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ). The intranuclear biophysico-chemical state of PPIns is still unclear, but several possibilities are emerging to explain how the acyl chains can be shielded from the nuclear aqueous environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of prostate cancer caused by PTEN deletion, PIK3CB knockout inhibited the development of prostate cancer, accompanied by a decrease in the level of AKT phosphorylation (Jia et al, 2008). Selective targeted inhibition of PIK3CB successfully blocked PI3K/AKT/mTOR signal transduction while avoiding target‐opening and off‐target effects of pan‐PI3K inhibitors (Mateo et al, 2017; Mazloumi Gavgani et al, 2021). In gastric cancer, PIK3CB mutation results in abnormal gene expression, leading to overactivation of the PI3K/AKT/mTOR signalling pathway, causing tumour cell proliferation and invasion (Elmenier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, PIK3CB mutation results in abnormal gene expression, leading to overactivation of the PI3K/AKT/mTOR signalling pathway, causing tumour cell proliferation and invasion (Elmenier et al, 2019). Mazloumi Gavgani et al (2021) found that in solid tumours, when PTEN is deficient, PIK3CB promotes the occurrence of tumours; for example, in endometrial cancer, PIK3CB is highly expressed and promotes the occurrence of endometrial cancer. In ESCC, reports regarding the role of PIK3CB are rare, and only Phillips et al (2006) examined the mutational status of PIK3CB in ESCC, showing that unlike PIK3CA, no mutations were detected.…”
Section: Discussionmentioning
confidence: 99%